The Impact of Digital Marketing on SMEs’ Growth in Azerbaijan - Sadigova, Matanat (ADA University, 2022)
The main objective of the study is to examine the impact of digital marketing adoption on SMEs’ growth in Azerbaijan. The research is conducted on the quantitative research method based on primary and secondary data sources to investigate this relationship. In this study, a questionnaire is used to collect quantitative data from the participants, whereas secondary data obtained from peer-reviewed articles, journals, statistics, reports and datasets. Quantitative data was analyzed using both the descriptive and inferential statistics. The descriptive statistics included frequency distributions, mean and standard deviation while the inferential statistics were multiple regression analysis, Pearson correlation coefficient and linearity test. The study population included 109 SMEs in Azerbaijan, with a focus on Baku, which constitute the sample size of this research by using random sampling method. The study findings indicate that social media marketing, mobile marketing, affiliate marketing, email marketing, search engine optimization (SEO) and Pay Per Click (PPC) all had a significant effect on SMEs’ growth in terms sales and brand awareness. The study results also showed a strong positive correlation between digital marketing and SMEs’ growth. The findings led to conclusion that the adoption of digital marketing techniques has a significant and positive effect on SMEs’ growth in terms of increasing sales and brand awareness. The study findings revealed that the lack of financial resources was the greatest challenge for SMEs in the adoption of digital marketing, followed by the lack of digital marketing knowledge and the lack of time for planning and implementation. The study recommended that SMEs should be trained and educated with the use of digital marketing techniques. The study also recommended that proper e-business policies should be implemented by the policy makers that help SMEs to adopt digital marketing. Lastly, the study recommended that SMEs should be provided with programs and financial support from government and public institutions in order to finance their digital marketing.
Keywords: Digital marketing.; SMEs.; SMEs’ growth.; Business